Exploring the underlying mechanism between fear of losing power and knowledge hiding - Iqbal, Omer; Ali, Zeeshan; Azam, Akbar (Frontiers in Psychology, 2022)
Drawing on the assumptions of approach/inhibition theory of power and conservation of resource of theory, this study aims to empirically explore the relationship between fear of losing power and knowledge hiding. To explicate the relationship, this study examines the mediating role of self-serving behavior and moderating role of personal competitiveness. To evaluate the relationships, a moderated-mediation model is devised and tested. Data is collected through a web-based questionnaire from 194 individuals employed in both manufacturing and service sector firms of Pakistan. We use multiple software packages to analyze the data. After employing several statistical techniques, the findings of the study suggest that self-serving behavior fully mediates the link between fear of losing power and knowledge hiding. Moreover, the result of two-way interaction reveals that personal competitiveness further amplifies the indirect relationship between fear of losing power and knowledge hiding through self-serving behavior. The present study is one of those few types that investigates and uncovers the hidden links between fear of losing power and knowledge hiding. Lastly, theoretical, and practical implications along with future research directions are discussed.